2016
DOI: 10.1038/srep32778
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-low thermal conductivities in large-area Si-Ge nanomeshes for thermoelectric applications

Abstract: In this work, we measure the thermal and thermoelectric properties of large-area Si0.8Ge0.2 nano-meshed films fabricated by DC sputtering of Si0.8Ge0.2 on highly ordered porous alumina matrices. The Si0.8Ge0.2 film replicated the porous alumina structure resulting in nano-meshed films. Very good control of the nanomesh geometrical features (pore diameter, pitch, neck) was achieved through the alumina template, with pore diameters ranging from 294 ± 5nm down to 31 ± 4 nm. The method we developed is able to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(109 citation statements)
references
References 82 publications
4
105
0
Order By: Relevance
“…One way of reducing the thermal conductivity of a bulk material without affecting the transport properties is through reducing its dimensionality [36], such as preparing thin films. This thermal conductivity reduction has been reported for several materials, such as SiGe [37][38][39]…”
Section: Introductionsupporting
confidence: 75%
“…One way of reducing the thermal conductivity of a bulk material without affecting the transport properties is through reducing its dimensionality [36], such as preparing thin films. This thermal conductivity reduction has been reported for several materials, such as SiGe [37][38][39]…”
Section: Introductionsupporting
confidence: 75%
“…Perez‐Taborda et al reported Si 0.8 Ge 0.2 nanomeshes with thermal conductivity down to 0.55 ± 0.10 W m −1 K −1 and n‐type Ag 2 Se film with 0.64 ± 0.10 W m −1 K −1 , being both obtained by 3ω‐SThM at room temperature. Si and SiGe nanowires were discovered to have size effects on thermal conductivity at 50 nm and 480 nm diameters respectively, when measured by 3ω‐SThM 147b…”
Section: Applicationsmentioning
confidence: 99%
“…13 The thermoelectric efficiency of any material system is related to dimensionless thermoelectric figure of merit ZT (= S 2 T /ρκ), where S , ρ, κ, and T are the Seebeck coefficient, electrical resistivity, thermal conductivity, and absolute temperature, respectively. High thermoelectric efficiency requires high Seebeck coefficient simultaneously with low electrical resistivity and thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%